Ceraspis jaliscoensis, a new species from México (Coleoptera: Scarabaeidae: Melolonthinae) - Delgado, Leonardo; Navarrete-Heredia, José Luis (Zootaxa, 2004)
A new Mexican species of Ceraspis LePeletier and Serville, C. jaliscoensis, from Jalisco state is described, and its male genitalia are illustrated. A key to the Mexican species of this genus and distribution maps of those species are included.